Intravascular lithotripsy in the treatment of coronary artery calcification in a high‐risk real world population. Issue 2 (8th January 2023) - Yeoh, Julian; Kanyal, Ritesh; Pareek, Nilesh; Macaya, Fernando; Cannata, Stefano; Tzalamouras, Vasileos; Webb, Ian; Dworakowski, Rafal; Melikian, Narbeh; Shah, Ajay M.; MacCarthy, Philip; Hill, Jonathan; et al.
Abstract: Background: The DISRUPT‐CAD study series demonstrated feasibility and safety of intravascular lithotripsy (IVL) in selected patients, but applicability across a broad range of clinical scenarios remains unclear. Aims: This study aims to evaluate the procedural and clinical outcomes of IVL in a high‐risk real‐world cohort, compared to a regulatory approval cohort. Methods: Consecutive patients treated with IVL and percutaneous coronary intervention at our center from May 2016 to April 2020 were included. Comparison was made between those enrolled in the DISRUPT‐CAD series of studies to those with calcified lesions but an exclusion criteria. Results: Among 177 patients treated with IVL, 142 were excluded from regulatory trials due to acute coronary syndrome presentation (47.2%), left ventricular ejection fraction <40% (22.5%), chronic renal failure (12.0%), or use of mechanical circulatory support (8.5%). This clinical cohort had a higher SYNTAX score (22.6 ± 12.1 vs. 17.4 ± 9.9, p  = 0.019), and more treated ACC/AHA C lesions (56.3% vs. 37.1%, p  = 0.042). Rates of device success (93.7% vs. 100.0%, p  = 0.208), procedural success (96.5% vs. 100.0%, p  = 0.585), and minimal lumen area gain (221.2 ± 93.7% vs. 198.6 ± 152.0%, p  = 0.807) were similar in both groups. The DISRUPT‐CAD cohort had no in‐hospital mortality, 30‐day major adverse cardiac events (MACE), or 30‐day target vessel revascularization (TVR). The clinical cohort had an in‐hospital mortality of 4.2%, 30‐day MACE of 7.8%, and 30‐day TVR of 1.5%. There was no difference in 12‐month TVR (2.9% vs. 2.2%; p  = 0.825). Twelve‐month MACE was higher in the clinical cohort (21.1% vs. 8.6%, p  = 0.03). Conclusion: IVL use remains associated with high clinical efficacy, procedural success, and low complication rates in a real‐world population previously excluded from regulatory approving trials.